KEBIJAKAN HUKUM LINGKUNGAN TENTANG PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) - Mukti, Widiani Agustien Wiguna; Suroya, Suci; Wahyudin, Rizky; Mubarok, Rihan Fathurahman; Kusyadi, Reiky Febrio Nayatama (Gapenas Publisher, 2024)
The enforcement of criminal environmental law against companies that dump B3 waste has been regulated in Law No. 32 of 2009 concerning Environmental Protection and Management, Articles 97 to 120 and also in Government Regulation No. 101 of 2014 concerning Waste Management of Hazardous and Toxic Materials, in addition to that it is also regulated in various other laws and regulations related to B3 waste. However, the implementation of rules through criminal environmental law enforcement against companies that dump B3 waste is still weak and not optimal, because it is constrained by various factors, both legal factors themselves where criminal sanctions are still used as a last resort in resolving waste pollution, law enforcement factors that are not firm with law enforcement officials and lack of human resources in the field of the environment from law enforcement officials. Factors of facilities and facilities that are not supportive, community and cultural factors, namely understanding the dangers of waste and legal compliance and awareness of the community are still lacking